Psychopedagogy and its contribution to the emotional state of students - Guerrero, Jacqueline Aracely Arteaga; Moreira, José Atilio Murillo; Zambrano, María José Zambrano; Briones, Marcelo Fabián Barcia; Quijije, Nelly Karina Arteaga (International research journal of management, IT and social sciences, 2022)
The arrival of psychopedagogy has made it possible to strengthen important areas of knowledge, to an endless number of needs identified in the field of education, plays an important role in teaching and learning, and its contribution to students is focused on psychological research interrelated with cognitive, social, and emotional processes. The role of the counselor is focused on prevention, detection, and intervention in the individual’s learning problems, improving their quality of life, especially from the field of emotions, with the practice of emotional intelligence. Therefore, the objective of this work is to analyze the contribution offered by psychopedagogy to the emotional state of students. For the research, the qualitative methodology was used, with a deductive and interpretive approach, applying the bibliographic-descriptive documentary method, based on the specialized literature obtained from reliable sources, which enabled the study to achieve a result that in Ecuador most cases are conducted from the intervention of educational psychologists and teachers, since the existence of professionals in the area (psychopedagogues) is scarce, becoming a demand for the profile in today’s society and a career to be promoted by higher education organizations.